Isolation and characterization of a new fungal species, Fusarium equiseti (Corda) Sacc., from Brassica juncea in Bharatpur - PD Meena; Riteka Gupta; Pankaj Sharma; PK Rai; HS Meena; SK Singh (Journal of Oilseed Brassica, 2026)
A field survey of emerging collar root disease incidence at farmer’s fields of Indian mustard (Brassica juncea L.) wasconducted in Bharatpur district of Rajasthan to confirm the casual organism of the disease. The pathogen from collecteddiseased samples was isolated, purified and supply to Agarkar Research Institute, Pune, India for identification. Analysisof the sequences of different fragments of the ribosomal genes demonstrated that isolated pathogen species belongs tothe Nectriaceae family and is genetically different from other morphologically similar species of Fusarium. This newspecies is unique in having colonies on PDA at 25oC+ 2oC, fast growing, rosy pink to vanacous, reverse pell leuteus tolight ochraceous. As per the micromorphology, hyphae was hyaline, smooth, pigmented and 2.75-4.77μm wide. Singlesporepure culture produced chlamydospores were intercalary, fusoid, hyaline and smooth walled. Although, macroconidiawere abundantly produced, fusoid, smooth walled, hyaline, foot cell present and sickle shaped, 2-septate with 14.59-45.48 x 2.88-4.10μm in size. Though, microconidia were fusoid, 1-septate and 2.5-2.67 x 2.67-13.7 μm in size. As per ourstudies, the fungus was morphologically identified as Fusarium equiseti (Corda) Sacc. (NFCCI 4564).